2017
DOI: 10.3390/nano7070151
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Silica Matrix as a Tool for Minimizing Dipolar Interactions in NiFe2O4 and ZnFe2O4 Nanoparticles

Abstract: NiFe2O4 and ZnFe2O4 nanoparticles have been prepared encased in the MCM (Mobile Composition of Matter) type matrix. Their magnetic behavior has been studied and compared with that corresponding to particles of the same composition and of a similar size (prepared and embedded in amorphous silica or as bare particles). This study has allowed elucidation of the role exerted by the matrix and interparticle interactions in the magnetic behavior of each ferrite system. Thus, very different superparamagnetic behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…), which are materials that include two types of transition metals, have stood out due to their robust catalytic activity as exhibiting significant potential applications in various fields. In particular, a few of them such as ZnFe 2 O 4 [13,14], NiFe 2 O 4 [15,16,17,18,19,20,21,22], CoFe 2 O 4 [23], MnFe 2 O 4 [24], Ni 1-X Co X Fe 2 O 4 [25], and NiCuZn ferrites [26] have been reported to be greatly promising in the electrical properties of gas sensors and humidity sensors. More interesting, NiFe 2 O 4 with various microstructures have been prepared so far to effectively detect acetone [14,15,16,17], ammonia [18], NO 2 [19], n-propanol [20], and triethylamine [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…), which are materials that include two types of transition metals, have stood out due to their robust catalytic activity as exhibiting significant potential applications in various fields. In particular, a few of them such as ZnFe 2 O 4 [13,14], NiFe 2 O 4 [15,16,17,18,19,20,21,22], CoFe 2 O 4 [23], MnFe 2 O 4 [24], Ni 1-X Co X Fe 2 O 4 [25], and NiCuZn ferrites [26] have been reported to be greatly promising in the electrical properties of gas sensors and humidity sensors. More interesting, NiFe 2 O 4 with various microstructures have been prepared so far to effectively detect acetone [14,15,16,17], ammonia [18], NO 2 [19], n-propanol [20], and triethylamine [21].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the NiFe bimetallic MOFs have been synthesized by metal Ni incorporation, which is further converted to ternary oxides of NiFe 2 O 4 . Song et al obtained hollow NiFe 2 O 4 microspindles from NiFe bimetallic MOFs, illustrating a high sensitivity for acetone detection [14]. Zhang et al prepared 1D α-Fe 2 O 3 /NiFe 2 O 4 heterojunction, which showed an improved response to acetone vapors using NiFe-bimetallic MOFs [39].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, using HCA as a coating ligand instead of TEG leads to a dispersion of nanoparticles inside the ordered silica structure. The CFO HS nanocomposite shows a decrease in the M r / M s value, indicating a reduction in the interparticle interactions among particles . Moreover, the reduction of coercivity indicates that the system becomes less anisotropic.…”
Section: Resultsmentioning
confidence: 98%
“…However, these materials possess certain drawbacks including low catalytic activity, low electronic conductivity, restricted sensitivity, and selectivity. In recent years, some bimetal oxides, such as ZnFe 2 O 4 , , NiFe 2 O 4 , CoFe 2 O 4 , and MnFe 2 O 4 , have become gas sensing materials because of their defect effects and excellent catalytic activity. As a particular cubic spinel material, various microstructures of NiFe 2 O 4 have been prepared to efficiently detect acetone, , ammonia, n -propanol, toluene, , NO 2 , etc.…”
Section: Introductionmentioning
confidence: 99%